Disability, hospitality and the new sharing economy. Issue 1 (8th January 2018) - Boxall, Kathy; Nyanjom, Julie; Slaven, Janine
Abstract : Purpose: This paper aims to explore the place of disabled guests in the new world of hotel and holiday accommodation shaped by the sharing economy. Design/methodology/approach: The paper uses Levitas's (2013 ) Utopia as Method as a methodological tool to develop the hypothetical future scenarios, which are used to explore the place of disabled guests in peer-to-peer holiday accommodation. Findings: Analysis of the hypothetical scenarios suggests that without state intervention, the place of disabled guests in both traditional hotels and peer-to-peer holiday accommodation is far from secure. Research limitations/implications: This is a new area and the authors' discussion is therefore tentative in its intent. Practical implications: Planners and policymakers should consult with, and take account of, the needs of disabled people and other socially excluded groups when regulating shared economy enterprises. It may be helpful to put in place broader legislation for social inclusion rather than regulate peer-to-peer platforms. Any recourse to markets as a means of resolving access issues needs also to acknowledge the limited power of socially excluded groups within both traditional and sharing economy markets. Social implications: The hypothetical scenarios discussed within this paper offer planners, policymakers and tourism stakeholders opportunities to think through the access and inclusion needs of disabled guests in the shared economy sector. Originality/value: The paper extends discussion of hospitality and disability access to include shared economy approaches and the place of disabled guests in the new world of holiday accommodation shaped by the sharing economy.